2016
DOI: 10.1177/1066480716648696
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supervised Filial Therapy Training on Attitude, Knowledge, and Skills

Abstract: Research in filial therapy has provided strong support for its efficacy in improving parent-child relationships. While studies have extensively examined the impact of filial therapy training on parent and child participants, to date, no study has examined the training experiences of filial therapists. Using a mixed methodological approach, we examined the impact of supervised filial therapy training on graduate counseling students' play therapy attitudes, knowledge, and skills. Twenty-three students voluntaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Child-centered play therapy is the theoretical foundation for CPRT, thus requiring similar attitudes, knowledge, and skills. Numerous studies have measured child-centered play therapy training using the PTAKSS (Crane & Brown, 2003; Kao, & Landreth, 1997; Lindo et al, 2012; Lindo, Meany-Walen, & Sullivan, 2012; Lindo et al, 2016; Meany-Walen et al, 2013; Muro, Holliman, Blanco, & Stickley, 2015). With this foundation, the primary author adapted the PTAKSS with permission (S. Kao, personal communication, July 27, 2015) for evaluating the impact of a 2-day CPRT training.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Child-centered play therapy is the theoretical foundation for CPRT, thus requiring similar attitudes, knowledge, and skills. Numerous studies have measured child-centered play therapy training using the PTAKSS (Crane & Brown, 2003; Kao, & Landreth, 1997; Lindo et al, 2012; Lindo, Meany-Walen, & Sullivan, 2012; Lindo et al, 2016; Meany-Walen et al, 2013; Muro, Holliman, Blanco, & Stickley, 2015). With this foundation, the primary author adapted the PTAKSS with permission (S. Kao, personal communication, July 27, 2015) for evaluating the impact of a 2-day CPRT training.…”
Section: Instrumentationmentioning
confidence: 99%
“…Research specific to the training of the therapist conducting the CPRT groups, however, has been very limited. Lindo et al (2016) conducted a study titled The Impact of Supervised Filial Therapy Training on Attitude, Knowledge, and Skills examining graduate students’ experiences and perceptions, and the degree to which the training influenced their understanding and proficiency in play therapy before and after a 15-week supervised filial therapy training. To date, the study by Lindo et al (2016) is the only known research focusing on the training aspect of either Filial therapy or CPRT.…”
mentioning
confidence: 99%
“…Similar to Crane and Brown (2003) and Lindo et al (2016), this flipped course yielded comparable p values in the Knowledge and Skills subscales. In this study, as hypothesized, the subscale that grew the most between September and December was the skills subscale.…”
Section: Discussionmentioning
confidence: 71%
“…In prior studies, neither Crane and Brown (2003) nor Lindo et al (2016) demonstrated statistical significance in the Attitudes scale. Crane and Brown suggested that this finding may be attributable to lower reliability and validity for this particular subscale.…”
Section: Discussionmentioning
confidence: 83%
“…In relation to our study, seeking supervision and consultation may be an identified preventive resource in the areas of social resourcefulness, scanning, and maintaining perspective. Supervision can be used to help counselors design and implement self‐care plans and strategies once signs of interpersonal stress or burnout are observed (Lindo et al., 2016). It can also be used to help counselors build counseling self‐efficacy (Moore et al., 2020).…”
Section: Discussionmentioning
confidence: 99%